Efficacy of Sunscreen Gel Infused with Giant Tiger Prawn (Penaeus monodon) Head Extract (Sciences of Pharmacy, 2023)
Excessive sunlight exposure can lead to various minor skin disorders, including sunburn and the development of chronic skin malignancies. One effective preventive measure against these adverse effects is the use of sunscreen. Sunscreen can be derived from natural sources, such as the astaxanthin compound in giant tiger prawns (Penaeus monodon). This study aimed to formulate a sunscreen gel from giant tiger prawn head extract that meets good physical gel standards. Additionally, the study sought to determine the sun protection factor (SPF), erythema transmission level (%TE), and pigmentation transmission level (%TP) through in-vitro testing. The extraction process involved using coconut oil as a solvent using the maceration method. The resultant extract was then evaluated for SPF, %TE, and %TP values and subsequently formulated into gel variants with extract concentrations ranging from 1% to 10%. The findings of this investigation revealed that the giant tiger prawn head extract exhibited SPF, %TE, and %TP values of 8.0±0.11, 18.8±0.25%, and 21.7±0.73%, respectively, categorizing it as providing maximum protection, facilitating fast tanning, and acting as a sunblock. The gel formula containing 8% giant tiger prawn head extract demonstrated the highest sunscreen potential. In conclusion, this study highlights the promising potential of giant tiger prawn head extract as a natural sunscreen ingredient and identifies the optimal gel formula for effective sun protection.